Symptom retention after successful intensive trauma-focused treatment for post-traumatic stress disorder - Frédérique A. M. Wesseling; Eline M. Voorendonk; Linda Rozendaal; Ad de Jongh (European Journal of Psychotraumatology)
Background: Evidence suggests that individuals undergoing successful treatment for post-traumatic stress disorder (PTSD) continue to experience PTSD symptoms.Objective: To determine the extent to which people continue to suffer from PTSD symptoms after intensive trauma-focused treatment and at six-month follow-up, despite no longer meeting diagnostic criteria for PTSD.Method: In total, 1015 individuals with PTSD participated in an eight-day intensive trauma-focused treatment programme combining psychoeducation, physical activity, prolonged exposure, and EMDR therapy. PTSD symptoms were assessed using the Clinician-Administered PTSD Scale for DSM-5 (CAPS-5) at baseline, post-treatment, and at six-months follow-up. Residual symptoms among those who no longer met PTSD diagnostic criteria were identified. Logistic regression analyses explored baseline predictors of the most persistent symptoms.Results: CAPS-5 total scores showed a significant reduction from pre- to post-treatment (d = 1.99) and remained improved at six-month follow-up (d = 1.48), despite a small to moderate increase in symptoms between post-treatment and follow-up (d = −0.38). Among those no longer meeting PTSD criteria post-treatment (75.8%) or at follow-up (63.2%), a substantial proportion (56.1% and 44.7% respectively) reported residual symptoms. The most frequently reported residual symptoms at six-months follow-up were negative beliefs (32.2%), negative feelings (28.7%), and intrusive memories (26.9%). The most persistent symptoms, based on odds ratios, were avoidance of thoughts or feelings (C1, OR = 38.38), intrusive memories (B1, OR = 25.00), and negative feelings (D4, OR = 22.12). Predictors of these residual symptoms included number of traumatic events, sexual trauma, suicidality, country of birth and receiving governmental income support.Conclusions: The results support growing awareness that, after seemingly successful trauma-focused treatment, a notable proportion of patients continue to suffer from specific PTSD symptoms. These findings underscore the importance of continued monitoring and tailored interventions targeting residual symptoms following treatment.